2017
DOI: 10.1002/hbm.23719
|View full text |Cite
|
Sign up to set email alerts
|

Partial volume model for brain MRI scan using MP2RAGE

Abstract: MP2RAGE is a T1 weighted MRI sequence that estimates a composite image providing much reduction of the receiver bias, has a high intensity dynamic range, and provides an estimate of T1 mapping. It is, therefore, an appealing option for brain morphometry studies. However, previous studies have reported a difference in cortical thickness computed from MP2RAGE compared with widely used Multi-Echo MPRAGE. In this article, we demonstrated that using standard segmentation and partial volume estimation techniques on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…Alternative approaches have been to normalize an MPRAGE scan by an additionally acquired gradient echo scan (Van de Moortele et al, 2009; Lüsebrink et al, 2013), or to using the MP2RAGE method, which similarly can remove this bias (Marques et al, 2010). However, these alternate acquisition schemes can influence the positioning of the cortical surface reconstruction (Fujimoto et al, 2014), and, due to nonlinear combination of the two inversion images used in MP2RAGE, assumptions of partial volume estimation algorithms used in morphometry studies may be violated (Duché et al, 2017). Nevertheless, these bias correction methods can greatly improve the robustness of the surface reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative approaches have been to normalize an MPRAGE scan by an additionally acquired gradient echo scan (Van de Moortele et al, 2009; Lüsebrink et al, 2013), or to using the MP2RAGE method, which similarly can remove this bias (Marques et al, 2010). However, these alternate acquisition schemes can influence the positioning of the cortical surface reconstruction (Fujimoto et al, 2014), and, due to nonlinear combination of the two inversion images used in MP2RAGE, assumptions of partial volume estimation algorithms used in morphometry studies may be violated (Duché et al, 2017). Nevertheless, these bias correction methods can greatly improve the robustness of the surface reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study by Madan () has shown that head motion can cause a significant decrease of numerical FD estimates. Moreover, just as reference values for blood tests may differ depending on the laboratory where they are measured, fractal analysis may be influenced by the type of scanning equipment, sequences, preprocessing software or estimation method, as has been shown for other morphometric analyses (e.g., Wonderlick et al, ; Madan & Kensinger, 2017; Duché et al, ). In this context, it is noteworthy that the MASSIVE and the MSC data were acquired on scanning systems from two different manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…2009; Madan and Kensinger 2017;Duché et al 2017. In this context, however, it is noteworthy that the MASSIVE and the MSC data were acquired on scanning systems from two dierent manufacturers.…”
Section: Discussionmentioning
confidence: 99%